Development of Project-Based Mathematics Learning Materials Integrating East Javanese Ethnomathematics to Improve Fourth-Grade Students' Geometry Learning Outcomes - Nasrudin, Muhammad; Mukhlis, Nurul Awaliyah; Lailiyah, Siti; Syaifudin, Mokhamad; Maulana Fahrudin, Tresna (Jurnal Pendidikan Matematika, 2025)
Many elementary students still struggle to connect mathematical concepts to real-life contexts, particularly in geometry, due to traditional teaching practices that rely on rote memorization rather than conceptual understanding. This study addresses these issues by developing project-based learning materials enriched with ethnomathematical content drawn from East Javanese culture to enhance fourth-grade students’ understanding of plane geometry. The research utilized the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) within a one-group pretest–posttest design involving 26 fourth-grade students from MI Unggulan Roudlotul Ulum, Sidoarjo. Data were collected through observations, interviews, questionnaires, tests, and documentation. Results indicated that the developed materials aligned well with curriculum requirements and student learning needs, incorporating cultural elements such as traditional games and crafts into project activities. Feasibility evaluations from content experts (92%), design experts (94%), and practitioners (90%) confirmed that the materials were highly valid and practical. The paired-sample t-test (p < 0.05) demonstrated significant improvements in learning outcomes, while qualitative feedback showed strong engagement, increased confidence, and cultural appreciation. These findings suggest that integrating ethnomathematics into project-based instruction can strengthen contextual learning, foster cultural awareness, and improve conceptual understanding in elementary mathematics education. Salah satu permasalahan yang sering muncul di sekolah dasar adalah kesulitan siswa dalam memahami dan mengaitkan konsep geometri bangun datar dengan pengalaman sehari-hari. Hal ini disebabkan oleh pendekatan pembelajaran yang masih berfokus pada hafalan rumus dan latihan mekanis, bukan pada pemahaman konseptual yang bermakna. Penelitian ini bertujuan untuk mengembangkan bahan ajar berbasis proyek (Project-Based Learning) yang dipadukan dengan muatan etnomatematika khas Jawa Timur untuk meningkatkan pemahaman konsep dan hasil belajar matematika siswa kelas IV pada materi bangun datar. Penelitian ini menggunakan metode penelitian dan pengembangan (Research and Development) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation) dan desain one-group pretest–posttest yang melibatkan 26 siswa MI Unggulan Roudlotul Ulum Sidoarjo. Data dikumpulkan melalui observasi, wawancara, angket, tes, dan dokumentasi. Hasil penelitian menunjukkan bahwa bahan ajar yang dikembangkan telah sesuai dengan kebutuhan belajar siswa serta capaian pembelajaran yang berlaku. Integrasi unsur budaya lokal seperti permainan tradisional engklek, pola batik, dan bentuk makanan khas daerah menjadikan pembelajaran lebih kontekstual dan menarik. Penilaian kelayakan oleh ahli materi, desain, dan praktisi menunjukkan kategori “sangat valid” sehingga bahan ajar layak digunakan dalam pembelajaran. Analisis uji-t berpasangan menunjukkan peningkatan hasil belajar siswa yang signifikan secara statistik (p < 0,05). Selain itu, siswa menunjukkan minat, keterlibatan, dan apresiasi tinggi terhadap budaya lokal selama proses pembelajaran. Temuan ini mengindikasikan bahwa integrasi etnomatematika dalam pembelajaran berbasis proyek dapat menjadi strategi efektif untuk memperkuat pembelajaran kontekstual, meningkatkan hasil belajar, serta menumbuhkan kesadaran budaya dan karakter siswa sejak dini.